National evaluation of the Transition Care Program RFT 206/0506: final evaluation report - Masters, Stacey; Giles, Lynne; Halbert, Julie; Stepien-Hulleman, Jackie; Eckermann, Simon; Prendergast, Justin; Whitehead, Criag; Cheney, Fiona; Crotty, Maria (Australian Government, 2008)
The Transition Care Program provided additional treatment and care options following hospitalization that were highly valued by patients and their families. Functional improvements occurred. When compared with similar groups of frail older people discharged from hospital during the same time period, those who received Transition Care had fewer readmissions to hospital and were less likely to move into permanent residential aged care. These outcomes are achieved at a comparatively high cost. For every day a recipient of Transition Care survives without institutional care i.e. without hospital or residential aged care over a six month period it costs $344 per day. Costs were evaluated during an early phase of the program when they are likely to be high. The program was implemented within a health context where older people across Australia have widely variable access to rehabilitation and geriatric hospital beds. It did not appear that areas which were short of aged care services or subacute beds had been prioritized in the allocation of the first 2,000 Transition Care places.